2004
DOI: 10.1590/s0074-02762004000800009
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi: inhibition of alpha-hydroxyacid dehydrogenase isozyme II by N-allyl and N-propyl oxamates and their effects on intact epimastigotes

Abstract: N-allyl (NAOx) and N-propyl (NPOx) N-allyl (Et-NAOx) and N-propyl (Et-NPOx) oxamates were tested as a possible trypanocidal prodrugs, in comparison with nifurtimox and benznidazole, the expected trypanocidal effects were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Similar results were obtained with homogenates of the five tested T. cruzi strains (results not shown). Previously, we had demonstrated that the esters (EtNAOx and Et-NPOx) were not inhibitors for the purified HADH-isozyme II [5].…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Similar results were obtained with homogenates of the five tested T. cruzi strains (results not shown). Previously, we had demonstrated that the esters (EtNAOx and Et-NPOx) were not inhibitors for the purified HADH-isozyme II [5].…”
Section: Resultsmentioning
confidence: 96%
“…It has been established that HADH-isozyme II is actually integrated into metabolic pathways supplying energy for the motility of flagellum and survival of the parasites [10], because this isozyme participates in the reoxidation of NADH during glycolysis [17], and in a shuttle system transferring reducing equivalents (NADH) from cytosol into the mitochondria [10]. Consequently, an inhibitor of HADH-isozyme II will not only inhibit glycolysis but will also inhibit the shuttle system, and therefore, it has been proposed that inhibitors of this isozyme could reduce the motility and survival of this parasite [5,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations